2011
DOI: 10.1123/tsp.25.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Riding the Wave of an Expert: A Successful Talent Development Environment in Kayaking

Abstract: The holistic ecological approach to talent development in sport highlights the central role of the overall environment as it affects a prospective elite athlete. This paper examines a flat-water kayak environment in Norway with a history of successfully producing top-level senior athletes from among its juniors. Principal methods of data collection include interviews, participant observations of daily life in the environment and analysis of documents. The environment was centered around the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 28 publications
9
116
0
9
Order By: Relevance
“…In addition, psychological skills, affective interpersonal relationships with coaches and teammates and rewards coming from this practice reinforce the engagement and maintenance of these in the sport. Investigations in various sporting environments have revealed results similar to those found in this study, corroborating that the encouragement from significant people (parents, siblings, guardians) and invitation from friends or colleagues are key to entry in this sport 9,16,[21][22][23][24][25] . In this perspective, it was found that when at least one family member is part of the sports microsystem, there is a more favorable transition into this environment.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, psychological skills, affective interpersonal relationships with coaches and teammates and rewards coming from this practice reinforce the engagement and maintenance of these in the sport. Investigations in various sporting environments have revealed results similar to those found in this study, corroborating that the encouragement from significant people (parents, siblings, guardians) and invitation from friends or colleagues are key to entry in this sport 9,16,[21][22][23][24][25] . In this perspective, it was found that when at least one family member is part of the sports microsystem, there is a more favorable transition into this environment.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover the tale provides in-depth insight into goal setting processes and how applied sport psychology is practiced. Additionally the section underlines once again that sport psychology delivery is social constructed and thus the SPC and the player are key to success as well as considering that the program is interrelated and affected by the talent development environment (Henriksen et al, 2011;Larsen et al, 2013). Gilbourne and Richardson (2006) paper on tales from the field in professional football similarly describes the provision of sport psychology from a personal perspective thus supporting the need for first person perspectives in order to describe the process of doing sport psychology.…”
Section: The Art Of Goal Settingmentioning
confidence: 99%
“…Several meta-analyses showed that roughly 90% of the studies with goal setting had a powerful and continuous effect on behavior (Carron & Hausenblas, 2005;Weinberg, Butt & Knight, 2001;Weinberg & Gould, 2007). In the light of this knowledge, and the fact that other sports seem more interested in using qualified psychological methods and find them useful (Henriksen et al, 2011, Abbott & Collins, 2004, the detainment of these barriers between professional football and sport psychology seems to be an obstacle for further improvement. Knowing that goal setting is a well-known and widespread phenomenon, we believe that, putting the subject back on the agenda, with a scientific program, might be one way of reducing this gap.…”
mentioning
confidence: 99%
“…Achieving this level of extensive social support and family involvement has the potential to keep young basketball players in the club throughout childhood and adolescence, potentially serving as future elite players (Baker, Deakin, & Cote, 2005;Côté et al, 2009;FraserThomas et al, 2010;Galatti, 2010;Henriksen et al, 2010Henriksen et al, , 2011MacDonald et al, 2011;Strachan et al, 2011), and increasing the possibility of lifelong sport participation (Côté et al, 2013;Silva, Galatti, & Paes, 2010). Thus, offering youth academies must go beyond the formation of professional athletes; it must promote human development in children and teenagers who seek the sport through an institutionalized extracurricular educational process (Côté et al, 2009;Fraser-Thomas et al, 2008;Paes & Galatti, 2013;Strachan et al, 2011).…”
Section: Lr Galatti J Côté Rs Reverdito V Allan Am Seoane Rr Paesmentioning
confidence: 99%
“…Vallée & Bloom, 2005) and sporting clubs (e.g. Henriksen et al, 2010;Henriksen, Stambulova, & Roessler, 2011). These studies highlight several features of settings that contribute to athletes' performances and participation including, among others, the importance of proximal role models, training that allows for diversification, and positive coachathletes relationships.…”
Section: Introductionmentioning
confidence: 99%